2007
DOI: 10.1016/j.cardiores.2007.03.002
|View full text |Cite
|
Sign up to set email alerts
|

A mutation in calsequestrin, CASQ2D307H, impairs Sarcoplasmic Reticulum Ca2+ handling and causes complex ventricular arrhythmias in mice

Abstract: The findings of the present study demonstrate that expression of mutant CASQ2(D307H) in the mouse heart results in abnormal myocyte Ca2+ handling and predisposes to complex ventricular arrhythmias similar to the CPVT phenotype observed in human patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 45 publications
(47 reference statements)
6
50
0
Order By: Relevance
“…One such protein is RyR2, where specific mutations result in a leaky RyR Ca 2+ release channel that can result in arrhythmiagenesis under stress conditions (Jiang et al, 2002;George et al, 2003;Lehnart et al, 2004;Kannankeril et al, 2006;Liu et al, 2006). Another series of mutations in calsequestrin (CSQ2) have been shown to induce leaky Ca 2+ release from the SR that is mediated at least in part by induction of increased RyR2 expression (Terentyev et al, 2003;di Barletta et al, 2006;Terentyev et al, 2006;Dirksen et al, 2007;Song et al, 2007). The role of CSQ in control of SR Ca 2+ release is emphasized by findings that overexpression of CSQ results in reduced Ca 2+ spark frequency and co-ordination, mirroring the effect of CSQ mutations on SR Ca 2+ release .…”
Section: Differential Properties Of Ca 2+ Sparks In Cardiac and Skelementioning
confidence: 99%
“…One such protein is RyR2, where specific mutations result in a leaky RyR Ca 2+ release channel that can result in arrhythmiagenesis under stress conditions (Jiang et al, 2002;George et al, 2003;Lehnart et al, 2004;Kannankeril et al, 2006;Liu et al, 2006). Another series of mutations in calsequestrin (CSQ2) have been shown to induce leaky Ca 2+ release from the SR that is mediated at least in part by induction of increased RyR2 expression (Terentyev et al, 2003;di Barletta et al, 2006;Terentyev et al, 2006;Dirksen et al, 2007;Song et al, 2007). The role of CSQ in control of SR Ca 2+ release is emphasized by findings that overexpression of CSQ results in reduced Ca 2+ spark frequency and co-ordination, mirroring the effect of CSQ mutations on SR Ca 2+ release .…”
Section: Differential Properties Of Ca 2+ Sparks In Cardiac and Skelementioning
confidence: 99%
“…Ventricular myocytes were isolated from CASQ2 D307H , CASQ2 null, and WT hearts by enzyme digestion, as before (4). Transmembrane ionic currents were recorded by whole cell patch-clamp experiments, as described previously (4).…”
Section: Methodsmentioning
confidence: 99%
“…Ventricular myocytes were isolated from CASQ2 D307H , CASQ2 null, and WT hearts by enzyme digestion, as before (4). Transmembrane ionic currents were recorded by whole cell patch-clamp experiments, as described previously (4). Experiments were performed either in patch-clamped or in permeabilized myocytes at room temperature (21 to 23°C) Whole cell patch-clamp recordings of transmembrane currents were performed using an Axopatch 200B amplifier (Axon Instruments) and pClamp-9 software.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are, however, many questions raised by this investigation that motivate future work. Previous studies did show expression of the mutant CASQ2 protein, but they demonstrated that the D307H mutation impairs monomeric CASQ2 binding to triadin or/and disrupts formation of polymeric CASQ2 (45)(46)(47). This loss of CASQ2 function in animals with the D307H mutation may accelerate CASQ2 protein degradation, and the disparities in CASQ2 abundance may depend on differences in the genetic background of the mice used in the various studies.…”
Section: Complexities In Casq2 Investigations and Future Studiesmentioning
confidence: 99%